GROWTH PERFORMANCE OF BROILER CHICKENS FED DIETARY LEVELS OF SWEET POTATO PEEL MEAL AS REPLACEMENT FOR MAIZE - Auta, Y. I.; Muhammad, A. S.; Sani, I.; Jama’a, N. A. (Nigerian Journal of Agriculture and Agricultural Technology, 2024)
The experiment was conducted to evaluate the growth performance of broiler chickens fed graded levels of sweet potato peel meal (SPPM) as replacement for maize. The treatment consists of five diets (0, 25, 50, 75 and 100%) formulated using SPPM as replacement for maize and coded as diets 1, 2, 3, 4 and 5 respectively, in both starter (23% crude protein) and finisher (20% crude protein) phases. Two hundred and twenty five broiler chicks were allotted to the diets in four replicates of fifteen chicks each in a completely randomized design (CRD). The feeding trial lasted for six weeks and feed and water were given ad libtum. Data were collected on initial weight, feed intakes and body weight changes. The result obtained at starter phase indicated significant (P<0.001) differences on all the productive performance parameters which include 218.25-364.45g final weight, 141.58-277.45g total weight gain, 6.74-13.21g daily weight gain, 2.19-3.98 feed conversion ratio and 0.25-0.46 feed efficiency) except on initial weight (76.67-87.00) and daily feed intake (24.76-28.90) were no significant difference was observed. The result at finisher phase further showed that, except on daily feed intake (82.54-110.66g) where no significant (P>0.05) difference was observed, a significant (P<0.001) difference was observed at fourth week (218.25-364.45g) and final (608.801278.10g) weights. Significant differences were found on total and daily weight gains, feed conversion ratio and feed efficiency with their values ranging between 390.55-913.65, 18.6043.51, 2.54-4.44 and 0.23-0.39 respectively. Overall phase followed similar trend as in starter phase where all the productive performance parameters were highly (P<0.001) significant with values ranging from 608.80-1278.10 (final weight), 532.13-1191.10 (total weight gain), 12.6728.36g (daily weight gain), 2.19-3.98 (feed conversion ratio) and 0.23-0.41 (feed efficiency) except on initial weight (76.67-87.00) and daily feed intake (53.66-69.78). However, the best value of feed conversion ratio was recorded on diet T1 (2.46), followed by diet T2 (3.01) while diet T3, T4 and T5 were statistically similar. It was concluded that SPPM can replace maize at 25% level in the diets of broiler chickens at both starter and finisher phase without affecting growth performance and is recommended for broiler chickens production in the study area.